Sintesis Mikroemulsi Menggunakan Surfaktan dan Minyak Atsiri Kulit Buah Jeruk Manis (Citrus sinensis) Sebagai Body Mist - Nurmalasari, Luluk; Suhendra, Lutfi; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): MaretDO - 10.24843/JRMA.2023.v11.i01.p02, 2023)
This study aims to determine the effect of the mixture ratio of surfactant (Tween 80: Tween 20: Span 80) and essential oil of sweet orange peel (Citrus sinensis) and determine the appropriate ratio of surfactant and sweet orange essential oil mixture to produce the best microemulsion characteristics. This study used a completely randomized design with phase 1 surfactant mixture ratio Tween 20: Tween 80: Span 80. The treatments used were 97:2,75:0,25; 97:2,50:0,50; 97:2,25:0,75; 97:2.00:1.00; 97:1,75:1,25. then step 2 the ratio of surfactant and sweet orange peel oil is 90:10; 87.5:12.5; 85:15; 82.5:17.5; 80:20. Data were analyzed using analysis of variance. The results showed that the ratio of the surfactant mixture Tween 20: Tween 80: Span 80 had an effect on the microemulsion characteristics of sweet orange peel oil. The best treatment on the surfactant mixture ratio 97:2,50:0,50 with the smallest turbidity index value, namely. The best ratio of surfactant and essential oil of sweet orange peel was 82.5:17.5 with turbidity index (%) before and after centrifugation 0.217±0.009% and 0.419±0.005%, respectively. It has a particle size of 26.5±14.2 nm, a zeta potential value of 0.0mV and is stable at pH 4.5, 5.5, and 6.5 for 8 weeks of storage.